Engineering mechanics: (mechanical science-I) - Chell, Gora Chand (Lakshmi Prakashani, 2011)
Engineering mechanics: (mechanical science-I) / Chell, Gora Chand. -- Kolkata: Lakshmi Prakashani, 2011 620.1 M741e4 4th ed. No. of Copies : 1